The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2174/1874210601811120987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angle and Type of Customized Abutment (Castable & Cast-to) on Torque Loss and Fracture Resistance After Cyclic Loading

Abstract: Background: Implant placement with more than 25° angle and use of customized abutments are still challenging in implant dentistry. Also, casting is still the most commonly used method for fabrication of customized abutments. Objective: This study evaluated the effect of angulation and type of abutment (castable and cast-to) on torque loss and fracture resistance after cyclic loading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Lee et al 27 and Atieh 28 found that the mode of failures often located at implant fixture and screw abutment. On the contrary, Shirazi et al 29 showed the fracture line located only at abutment screw. In this study, the failures were located at fixtures and abutment screws in CN group, but predominantly involved abutments and abutment screws fracture in other groups ( Table 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…Lee et al 27 and Atieh 28 found that the mode of failures often located at implant fixture and screw abutment. On the contrary, Shirazi et al 29 showed the fracture line located only at abutment screw. In this study, the failures were located at fixtures and abutment screws in CN group, but predominantly involved abutments and abutment screws fracture in other groups ( Table 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…When the inter-occlusal space is restricted, implants are placed outside of the arch, and the implant angle exceeds 30°, cast abutments can be employed. These abutments are also economically priced [18,19]. Cast abutments are classified into two types: cast-to and castable.…”
Section: Discussionmentioning
confidence: 99%